Different habitats of ferns growing in the Amonkoton stream, Zerafshan Valley, Uzbekistan - DILSHODJON MUMINOV; KHISLAT KHAYDAROV; KHOLMUROD ZHALOV; MURTOZA HASANOV; RANO ABDUMUMINOVA; ULUGBEK OCHILOV (Society for Indonesian Biodiversity, 2024)
Abstract. Muminov D, Khaydarov K, Zhalov K, Hasanov M, Abdumuminova R, Ochilov U. 2024. Different habitats of ferns growing in the Amonkoton Stream (Zerafshan Valley), Uzbekistan. Biodiversitas 25: 2696-2704. The Zerafshan Valley, Uzbekistan, characterized by a warm and arid climate, has declined vegetation and soil quality over recent decades, marking a stark departure from its once lush past. Understanding the nuanced relationship between species and their habitat is imperative to unraveling this ecological transformation. This research delves into ferns, which are highly responsive to environmental factors, seeking to elucidate their circumstances within the changing ecosystem. Through strategically planned intensive transects and plots as proxies for fern growth and habitat analysis, statistical methods like the Shannon-Wiener Index (H) and Bray-Curtis index were deployed. The climate-related information analysis was conducted using the CRU TS 4.07 tool. We made use of average temperatures and precipitation over 120 years. The results of analyses have been acquired from 490 fern individuals belonging to 13 species, 7 genera, and 6 families. There are four species: Equisetum arvense L., Equisetum ramosissimum Desf., Cystopteris fragilis (L.) Bernh. and Adiantum capillus-veneris L. were employed as indicators of habitat. The findings underscore a substantial decline in fern-populated areas, resulting in diminished diversity and abundance and a relatively high rarity level. Furthermore, a latitudinal correlation with ferns along the stream direction is exhibited by four indicator species, offering valuable insights into the intricate dynamics of the Zerafshan Valley's ecosystem.